The association of FDG-PET (SUVmax) and inflammatory marker in predicting tumour aggressiveness - Ahmad Saad, Fathinul Fikri; Abdullah, Noraini Sarina; Shaharuddin, Shazreen; Nordin, Abdul Jalil (Universiti Putra Malaysia Press, 2018)
Chronic inflammation is associated with processes that contribute to the onset or progression of cancer. This study examined the correlation between dichotomised patients with malignant tumours and inflammatory markers based on the altered glucose metabolism measured by the FDG SUVmax that underpins the degree of tumour aggressiveness. Thirty-one patients underwent 18F-FDG PET/CT for various carcinoma along with blood inflammatory markers such as C-reactive protein (CRP), interleukin-6 (IL6), lipid profile and fasting blood glucose (FBG) levels were obtained in retrospective study. Patients were dichotomised by the cut-off SUVmax value of 6.0 dl/ml derived from curve analysis (P=-0.025). The mean age of the subjects were 53.16 ± 12.06 years and mean SUVmax of 8.80±6.27 g/ml. Significant correlation was noted between the SUVmax and CRP and IL6 (r=0.361; P<0.05) and IL-6 with BMI and FBG with r=0.38; p<0.05 and r=0.34; p<0.05 respectively. The odds ratio (95% confidence intervals) for patients with the SUVmax cut-off 6.0dl/ml was predicted by FBG (OR:0.385, p<0.05) and the SUVmax > 6.0 dl/ml was inversely related to IL-6 (OR: 0.049, with p<0.005). Serum inflammatory markers and endogenous glucose are associated with a potentially more aggressive malignant cancer. In particular, IL6 may be used as a useful surrogate marker for tumour aggressiveness with an important prognostic value.